373 ADONHERS (AGED DONOR HEART RESCUE BY STRESS ECHO) PROTOCOL FOR HEART DONATION FROM MARGINAL DONOR HEARTS: MONOCENTRIC RETROSPECTIVE STUDY ON RECIPIENT'S SURVIVAL AFTER 10-YEAR FOLLOW-UP. (15th December 2022) - Mandoli, Giulia Elena; Barilli, Maria; Ghionzoli, Nicolò; Cameli, Matteo
Abstract: Backgorund: Amelioration of therapies and increased survival in heart failure (HF) is leading to a growing number of patients affected by advanced HF, with an overall 1-year prognosis ranging from 25 to 75%. The gold standard treatment for end stage HF is heart transplantation (Htx), but lack of organs donors remains an important limitation. Marginal hearts can potentially improve and be utilized after a re-evaluation by "aggressive" assessment of donor left ventricular function. Purpose: In our study we analysed if recipients of marginal donor hearts, selected by dipyridamole stress echocardiography, had different outcome compared to recipients with acceptable donor hearts. Methods: Data collected from 2006 and 2014 of patients who received orthotopic Htx from marginal heart donors (group 1) and were retrospectively analysed and compared with recipients of acceptable heart donors (group 2). Bedside standard echocardiography and dipyridamole stress echo was performed for the selection of marginal hearts > 55 years old or < 55 with comorbidities/mildly dysfunctional left ventricle. Clinical, laboratory and instrumental features of the two groups of recipients were evaluated and patients with homogenous baseline characteristics were selected to reduce biases among the two groups. Follow-up through routine heart transplant surveillance included visit, echocardiography, blood tests, serial endomyocardial biopsies and coronary angiography. Results: Twenty-two recipients were included in the study. Mean donors age was 41 ± 23, 45 ± 29 years for group 1 vs 36 ± 12 for group 2. The average follow-up was 113 months. Age, cardiovascular risk and morpho-functional characteristics of the left ventricle were comparable between the two population (P> 0.05). Left atrial size was significantly higher in marginal hearts (Optimal: p=0.007; Marginal: p=0.003). Acceptable recipients showed a higher impact of CAV (p= 0.019) together with more elevated values of cholesterol and triglycerides (p = 0.048 and p = 0.012 respectively). No differences concerning cellular or humoral rejection were found between the two groups. Four patients deceased, 3 had received a standard donor heart and 1 was from the marginal donor group, with and overall median time to death of 124 months. Conclusions: Our small pilot study shows how the evaluation of marginal donor hearts with echo stress result to no affect recipients survival compared with controls of acceptable hearts. A well-controlled selection of marginal hearts could therefore improve the shortage of organs, reducing the long line of patients waiting for a heart.